Uji Efektivitas Suspensi Baculovirus oryctes dan Metarhizium anisopliae (Metch.) Sorokin Terhadap Brontispa longissima Gestro. (Coleoptera :Chrysomelidae) di Laboratorium - Holong Erixon M; Syahrial Oemry; Fatimah Zahara (Jurnal Agroekoteknologi, 2015)
The objective of this research was to study the effectifity of suspension Baculovirus oryctes andMetarhizium anisopliae (Metch.) Sorokin to control Brontispa longissima Gestro.(Coleoptera : Chrysomelidae). The research was held at the laboratory of plant pest,Agroecotechnology Program Study, Agricultural Faculty, University of Sumatra Utara, Medan onApril to Mei 2014. This methode used Randomized Complete Design (RAL) of non Factorial thatconsist of 7 treatments and 4 replications. The research treatments were: 1. T0 : control(500 mL aquadest) 2. T1 : 40 ml B. oryctes / 500 mL aquadest 3. T2 : 50 ml B. oryctes / 500 mLaquadest 4. T3 : 60 mL B. oryctes / 500 mL aquadest 5. T4 : 40 gr M. anisopliae /500 mLaquadest 6. T5: 50 gr M. anisopliae / 500 mL aquadest 7. T6 : 60 gr M. anisopliae / 500 mLaquadest. The results showed that the highest percentage of mortality on T6(60 gr M. anisopliae / 500 mL aquadest) was about 95.00% and the lowest on T1(40 ml B. oryctes / 500 mL aquadest) was about 60.00%.Keywords : Effectifity, Baculovirus oryctes, Metarhizium anisopliae, Brontispa longissima